Ultrafast light-induced magnetization in non-magnetic films: from orbital and spin Hall phenomena to the inverse Faraday effect - Hamamera, Hanan; Souza Mendes Guimarães, Filipe; dos Santos Dias, Manuel; Lounis, Samir (Frontiers in Physics, 2024)
The field of orbitronics has emerged with great potential to impact information technology by enabling environmentally friendly electronic devices. The main electronic degree of freedom at play is the orbital angular momentum, which can give rise to a myriad of phenomena such as the orbital Hall effect (OHE), torques and orbital magnetoelectric effects. Here, we explore via realistic time-dependent electronic structure simulations the magnetic response of a non-magnetic material, an ultrathin Pt film, to ultrafast laser pulses of different polarizatons and helicities. We demonstrate the generation of significant orbital and spin magnetizations and identify the underlying mechanisms consisting of the interplay of the OHE,